PHRASEOLOGICAL UNITS RELATED TO EDUCATION IN ENGLISH AND UZBEK LANGUAGES - Bobonazarova Mukhlisa Yamgir kizi (Web of Journals Publishing, 2025)
This article examines phraseological units related to education in English and Uzbek languages, analyzing their meanings, cultural significance, and linguistic characteristics. The study reveals that English idioms often emphasize the effort and struggle involved in learning, while Uzbek phraseology highlights wisdom, moral development, and teacher respect. A comparative analysis demonstrates similarities and differences, reflecting distinct cultural attitudes toward education. Understanding these phraseological units enhances cross-cultural communication and contributes to linguistic studies.
Keywords: Phraseological units, education, idioms, English language, Uzbek language, comparative analysis, culture, wisdom, learning, knowledge.